2022
DOI: 10.1111/jfbc.14233
|View full text |Cite
|
Sign up to set email alerts
|

Piper retrofractum extract and its component piperine promote lymphangiogenesis via an AKT ‐ and ERK ‐dependent mechanism

Abstract: Administration of Piper retrofractum extract (PRE) has been reported to alleviate edema, but the mechanism underlying this effect is unknown. Promotion of lymphangiogenesis is known to improve lymphedema, but the effect of PRE on lymphangiogenesis remains unclear. In the present study, we investigated whether PRE and specifically, piperine, the main component of PRE, can induce lymphangiogenesis. Treatments with PRE and piperine significantly promoted the proliferation, migration, and tube formation in human d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several studies highlight the efficacy of Chinese herbal extracts and monomers in alleviating lymphedema by promoting lymphangiogenesis. Ishii et al ( 88 ) reported that piper retrofractum extract and piperine, isolated from piper retrofractum, notably enhanced the proliferation, migration and tube formation in human dermal lymphatic microvascular endothelial cells, thereby promoting lymphangiogenesis through the AKT and ERK pathways and effectively alleviating lymphedema. T total saponin of Panax notoginseng (PNS) can markedly promote lymphangiogenesis, and its mechanism may be related to the activation of the ERK1/2, PI3K and P38-MAPK signaling pathways, which stimulate the release of VEGF-C. PNS is a promising therapeutic option for managing secondary lymphedema or other lymphatic system disorder ( 89 ).…”
Section: Traditional Chinese Medicine Regulating Lymphangiogenesismentioning
confidence: 99%
“…Several studies highlight the efficacy of Chinese herbal extracts and monomers in alleviating lymphedema by promoting lymphangiogenesis. Ishii et al ( 88 ) reported that piper retrofractum extract and piperine, isolated from piper retrofractum, notably enhanced the proliferation, migration and tube formation in human dermal lymphatic microvascular endothelial cells, thereby promoting lymphangiogenesis through the AKT and ERK pathways and effectively alleviating lymphedema. T total saponin of Panax notoginseng (PNS) can markedly promote lymphangiogenesis, and its mechanism may be related to the activation of the ERK1/2, PI3K and P38-MAPK signaling pathways, which stimulate the release of VEGF-C. PNS is a promising therapeutic option for managing secondary lymphedema or other lymphatic system disorder ( 89 ).…”
Section: Traditional Chinese Medicine Regulating Lymphangiogenesismentioning
confidence: 99%